The Poet as Believer: A Theological Study of Paul Claudel. - Flannery, Michael A. (Fides et historia, 2013)
The article reviews the book "The Poet as Believer: A Theological Study of Paul Claudel," by Aidan Nichols, part of the Ashgate Studies in Theology, Imagination and the Arts series.